The Response of Estuarine Ammonia-Oxidizing Communities to Constant and Fluctuating Salinity Regimes - Santos, João Pereira; Sousa, António G. G.; Ribeiro, Hugo; Magalhães, Catarina (Frontiers in Microbiology, 2020)
Nitrification is a fundamental nitrogen biogeochemical process that links the oxidation of ammonia to the removal of fixed nitrogen in eutrophicated water bodies. Salinity can affect nitrification performance, yet there is still a lack of information on the ammonia oxidizers community behaviour facing daily salinity fluctuations. In this work, we address this gap by studying the effect of different salinity regimes on the activity and diversity of ammonia-oxidizing prokaryotes. Laboratory experiments were performed by exposing upstream and downstream estuary sediments to constant and fluctuation salinity regimes. Results indicated that daily salinity fluctuation regime had a negative effect on both AOB and AOA community’s diversity and on nitrification activity from upstream sediments while no effect on downstream sediments. Constant salinity regime showed clearly higher rates of nitrification in upstream sediments and a similar nitrification performance between the two salinity regimes in the downstream site. Phylogenetically, the estuarine downstream samples were dominated by AOA (2.26-3.48%) followed by NOB (0.99-1.96%) and, then, AOB (0.86-1.57%); whereas NOB dominated estuarine upstream sediment samples (1.40-9.52%), followed by AOB (1.09-2.22%) and AOA (0.40-0.59%). Analysis of variance identified the spatial difference between samples (downstream and upstream) as the main drivers of AOA and AOB diversity and activity response to the different salinity regimes. Our study indicates that communities from the different sites presented different plasticity toward the salinity regimes tested. These findings help to improve our understanding in the dynamics of the N cycle in estuarine systems by showing the resilience and consequently the impact of different salinity regimes on the diversity and activity of ammonia oxidizer communities.